Pathogenesis of Type - 1 Diabetes Mellitus; Diabetic Ketoacidosis - Aditi Goyal; Samarth Shukla (A Concise Clinicopathological Handbook of Diabetes Mellitus, 2021)
Diabetes refers to a group of conditions characterized by a high level of blood glucose. Too much sugar in the blood can cause serious, sometimes life threatening health problems. There are two types of chronic diabetic conditions: Type 1 and Type 2. In type 1 diabetes, the beta cells are destroyed by one’s own immune system leading to reduced insulin production and eventually hyperglycemia. Diabetic Ketoacidosis is an acute and potentially life-threatening complication of mainly type 1 diabetes, and is caused by critically low insulin levels, more often caused when further stress triggers the diabetic individuals like infections, cardiovascular events etc.